The suitability of industrial property legislation with the requirements of joining the World Trade Organization (Journal of the College of Basic Education, 2022)
The development of any country depends on creativity, innovation, invention, and preparation of legal and material issues that guarantee their peacefulness and independence in their work. The importance of intellectual products can be determined by the amount of money, equipment and labor required by the commercial and industrial activities in these sectors based on intellectual production. Countries have to include sort of legal framework to protect intellectual property. This reflects on their innovation and knowledge along with intellectual and innovative developments around the world. These developments indicate the deep need for intellectual property laws which form the main legal system that maintains State’s economy. TRIPS Agreement, throughout its articles, demonstrated the criteria related to providing intellectual property rights, its acquisition, and its maintenance along with the procedures of dispute settlement and prevention